1982
DOI: 10.1093/ajcn/35.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slimming and composition of diets on VO2 and thyroid hormones in healthy subjects

Abstract: Oxygen consumption and plasma thyroid hormone concentrations are modified by both low- and high-calorie diets. It has been suggested that the trigger may be changes in weight ("adipostatic" hypothesis involving the difference between the actual weight and the "set point") or changes in amount of carbohydrate in the diet ("carbohydrate" hypothesis). Two experiments were performed in order to test both hypotheses. Fourteen young healthy volunteers were studied: 1) at their spontaneous stable weight; 2) while los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…Nev ertheless, the bulk of studies of metabolic rate in animals on restricted diets deal with total caloric restriction. It has been suggested that increasing carbohydrate content of a re stricted diet could prevent the energy conser vation mechanism [26], a hypothesis which has not been confirmed [27]. Although the exact mechanism by which energy conserva tion occurs is not known, hormonal influences such as decreased thyroid activity [28] and decreased sympathetic nervous system activi ty [29] were described.…”
Section: Discussionmentioning
confidence: 99%
“…Nev ertheless, the bulk of studies of metabolic rate in animals on restricted diets deal with total caloric restriction. It has been suggested that increasing carbohydrate content of a re stricted diet could prevent the energy conser vation mechanism [26], a hypothesis which has not been confirmed [27]. Although the exact mechanism by which energy conserva tion occurs is not known, hormonal influences such as decreased thyroid activity [28] and decreased sympathetic nervous system activi ty [29] were described.…”
Section: Discussionmentioning
confidence: 99%
“…This early loss of protein is probably a consequence of adaptive hormonal responses which reduce the rate of protein synthesis. It occurs at a time of reduced availability of biologically active triiodothyronine [28,29] and possible increased resistance of metabolic rate to T 3 [30], The reduction in REE immediately af ter the start of caloric restriction can also be abolished by restitution of the reduced sym pathetic drive (using laevodopa) without al tering the rate of weight loss [9].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies 44 " 4 * and clinical observations 5 47 suggest that negative energy balance may be more closely related to the fall in blood pressure than are changes in body fat. Factors that have been or should be considered contributors to the hypotensive response to weight reduction include the fall in levels of insulin, 43 -** triiodothyronine, 49 and sympathetic nervous system activity 44 ; changes in intake of sodium, 33 potassium, 34 calcium, 35 x fat, 37 alcohol, 38 and foods of animal origin 39 " 41 ; altered exercise patterns 50 ; and -as yet untested -changes in lean body mass. Pending the availability of appropriate prospective studies to clarify the hemodynamic response to weight reduction, the results of the present investigation warrant caution in the assumption that body fat itself is a major determinant of blood pressure level among obese hypertensive individuals.…”
mentioning
confidence: 99%